Survival rates for Nephrops norvegicus discarded from Northern European trawl fisheries. (16th March 2020) - Fox, Clive J; Albalat, Amaya; Valentinsson, Daniel; Nilsson, Hans C; Armstrong, Frank; Randall, Peter; Catchpole, Thomas
Abstract: When discarded from bottom trawl fisheries, survival of Nephrops norvegicus may be sufficiently high that this species can be exempted from the EU Landing Obligation. In three studies, Nephrops were sampled from trawlers in northern European waters, and the fate of individuals monitored for a minimum of 13 days in onshore tanks. Winter estimates of captive survival (means ± 95% confidence intervals), including immediate mortality during catch sorting, were 62 ± 2.8% for the West of Scotland, 57 ± 1.8% for the Farne Deeps (North Sea), and 67 ± 5.4% for the Skagerrak. The Farne Deeps fishery is not active in summer, but captive survival rates in summer in the other two areas were reduced to 47 ± 3.4% for West of Scotland and 40 ± 4.8% for the Skagerrak. Linear modelling of the West of Scotland and Skagerrak data suggested that higher survivals in winter were related to colder water or air temperatures, although temperatures during captive observation may also have had an impact. Net modifications in the Skagerrak study had an effect on survival, which was higher for Nephrops sampled from nets equipped with the more selective Swedish sorting grid compared to Seltra trawls.